2021
DOI: 10.3390/polym13101636
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Polyesters with Alkene and Carboxylic Acid Side-Groups for Tissue Engineering Applications

Abstract: Main chain polyesters have been extensively used in the biomedical field. Despite their many advantages, including biocompatibility, biodegradability, and others, these materials are rather inert and lack specific functionalities which will endow them with additional biological and responsive properties. In this work, novel pH-responsive main chain polyesters have been prepared by a conventional condensation polymerization of a vinyl functionalized diol with a diacid chloride, followed by a photo-induced thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This observation reflected the elimination of short chains in the ester linkage . Simultaneously, the peaks at 725.32 cm –1 were attributed to the carbon–carbon chain of the carboxylic group on the fabric’s surface …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This observation reflected the elimination of short chains in the ester linkage . Simultaneously, the peaks at 725.32 cm –1 were attributed to the carbon–carbon chain of the carboxylic group on the fabric’s surface …”
Section: Resultsmentioning
confidence: 89%
“…39 Simultaneously, the peaks at 725.32 cm −1 were attributed to the carbon−carbon chain of the carboxylic group on the fabric's surface. 40 The hydrolysis of PES showed a significant weight loss of 25.36% when the NaOH concentration was raised to 21 wt %, as seen in Figure 2c. According to a past study, a weight loss from 15 to 30% could contribute to overall depreciation in stiffness, tenacity, and elongation of PES fabrics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This effect can be correlated with the presence of the pendant carboxylic acid groups that can undergo condensation or decarboxylation upon thermal heating. 47 Acid-Triggered Degradation of Functionalized Polylactides Containing Acetal Units. In our previously published work, 22 we proved that the random distribution of acetal units (27 mol %) in the polylactide chain enabled the degradation of copolymers within 72 h.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The TGA results showed that only the copolymer modified with thioglycolic acid had a lower T max compared to the nonmodified one. This effect can be correlated with the presence of the pendant carboxylic acid groups that can undergo condensation or decarboxylation upon thermal heating …”
Section: Resultsmentioning
confidence: 99%
“…In this work, we aim to develop an open-loop recycling strategy by synthesizing new types of high value-added biodegradable polymers rather than generating conventional C-rPET to address the issue of high PET-recycling cost. For this purpose, we attempted to develop BHET-based biodegradable copolymers with excellent physical and mechanical properties that the conventional semicrystalline PET does not retain. The BHET-based biodegradable polymers were synthesized from BHET with various types of hydrophilic aliphatic carboxylic acids, including succinic acid (C4, SA), adipic acid (C6, AA), sebacic acid (C10, Seb), and dodecanedioic acid (C12, DDDA), via a two-step melt polycondensation reaction to create aromatic–aliphatic poly­(ethylene aliphatate- co -terephthalate) random copolymers with increased biodegradability. The representative monomer species utilized in this study are summarized in Table . The relationship between the chain structure of the aromatic–aliphatic random copolymers and their thermo-mechanical properties was investigated.…”
Section: Introductionmentioning
confidence: 99%